ANALISIS PENYEBAB KETIDAKLENGKAPAN PENGISIAN INFORMED CONSENT DI RSUD dr. ABDOER RAHEM SITUBONDO - Irene Anjar Pratiwi; Efri Tri Ardianto; Atma Deharja; Indah Muflihatin (Politeknik Negeri Jember, 2022)
The incompleteness of informed consent in general surgery cases inpatients at dr. Abdoer Rahem Situbondo hospital has an increase every month in the first trimester of 2019. The highest increase occurred in March, which was 74% from the previous 64% in February. Based on the Minister of Health of the Republic of Indonesia No. 129 of 2008, the minimum standard for filling out informed consent is 100%. The purpose of this research was to analyze the factors causing the incomplete filling of informed consent in inpatient general surgery cases at Dr. Abdoer Rahem Situbondo using Simamora's performance theory. The type of this research is qualitative analysis. The research design used is action research. Data collection techniques used were interviews, questionnaires, documentation, CARL (Capability, Accessibility, Readiness, Leverage), and brainstorming. The preliminary study was carried out from January to February 2020. Data collected were an inpatient general surgical case informed consent form, which had been returned to the medical record unit. The results obtained from this research are that there has never been an evaluation of informed consent’s incompleteness. No award was given for the performance of completeness informed consent. There has never been any learning such as a seminar or training on filling out the informed consent.